Body Mass Index, Physical Activity Status and Sleep Duration of Elderly - Fajrah Ilsya, Marisa Noviyanti; Resmana, Dadan; Hasan, Muhamad Fahmi; Ramania, Nia Sri; Safei, Imam (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Regular physical activity by vulnerable populations such as the elderly can improve physical and mental function and reduce the risk of dementia. However, awareness of doing physical activity is still low among the elderly, especially in the city of Bandung. Therefore, this study aims to determine the level of physical activity, BMI, and sleep duration of the elderly in the city of Bandung. This study used a quantitative descriptive method without a control group and assessed the level of physical activity using the International Physical Activity Questionnaire. The results of this study indicate that the average (SD) age, height, weight, and BMI of the study subjects were 56.88 ± 5.32 years, 155.8 ± 7.66 cm, 66.84 ± 12.46 respectively kg, and 27.8 ± 3.8 kg/m2. Meanwhile, the average physical activity status and sleep time of the research subjects were 452.68 ± 76.88 METs, and 344.48 ± 46.28 minutes, respectively. The conclusion of this study shows that the elderly in Kiaracondong District, Bandung City, West Java Province have a low level of physical activity and are in the category of obesity or overweight. However, the resulting sleep duration is still included in the recommended category. Keywords: elderly, physical activity, west java